Os conflitos no ambiente sociomoral escolar e suas implicações na construção das relações de cooperação - Farias, Cristina Helena Bento (2010)
This work is part of the Research Line School Practice and Public Policy Program Graduate Education UFSM. The central theme of the study were the conflicts in the school environment sociomoral and its implications in cooperative relations that sense, the goal was to understand how to resolve conflicts on the environment sociomoral escoalr involves building cooperative relationships. The methodology included a qualitative approach, using the perspective of the case study. The studies of Piaget (1993, 1994, 1998), DeVries and Zan (1998), and Moreno Sastre (2002), Puig (1998;2007), among others, served as the theoretical development of the research. Data collection was conducted through semi-structured interview with two teachers, a representative of the direction and guidance counselor in an elementary school, the private network of the city of Santa Maria. Data analysis was through two categories: the conflicts in the school environment and relationships sociomoral cooperation.The of analyzing the data, we concluded that the lack of knowledge of teachers and managers, on conflicts and their contribution for student learning is a limitation for the educational work related to building cooperative relationships. Thus, we find that the concept of conflict and the way in which teachers act are dependent on each other. When designing the conflict as something negative, focus on the product, that is the resolution itself.Thus were we need to promote opportunities for training for teachers to reflect and rethink their ideas about conflicts and to educate on the importance of building cooperative relationships so that they can effectively contribute in the formation of autonomous subjects.